The main directions of improving acoustic intelligence devices - Олейников, А.Н.; Бородавка, А.В. (Radiotekhnika, 2017)
Directional microphones are the most popular devices for acoustic intelligence. Development and improvement of directional microphones can be divided into three stages: “acousto-mechanical” stage, analog signal processing stage, digital signal processing stage. Digital signal processing has a significant influence on the directional microphones development. If super-directive arrays are using as sub-arrays, directivity index will be increased at low frequencies. Advantage in 6 dB increases distance of recording two times.